The Role of Cloud Computing in Education: Saudi Arabian Study - Al- Rasheedi, Gareebah; Khan, Nabeel (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Education is a crucial factor in ensuring sustainable progress, In particular, for countries with growing economies. Due to resource virtualization, Cloud computing has both the Internet and complex scalability. Both public and private learning institutions should take advantage of the potential benefit of cloud infrastructure to ensure high-quality service regardless of the minimum resources available. Because of its numerous advantages, cloud computing is taking center stage in academia. This research will seek to establish the benefits associated with the use of cloud computing in education. Cloud technology solutions ensure research and development as well as teaching, and its more sustainable and efficient, thereby having a positive impact on the quality of teaching and learning in educational institutions. The goal of this research is to identify the benefits of cloud computing usage in education. Cloud technology solutions make research and development as well as teaching more competitive and effective, thereby having a positive impact on the quality of education.